Optimalisasi Keuntungan Jus Sandra Menggunakan Pemrograman Linear Melalui Metode Simpleks - Hendry Mulya Susanto; Heriyanto; Nichero Giordany; Riyan Costa; Winskey Sudarmo; Dudy Effendy (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
Abstract Jus Sandra, is one of the Micro, Small and Medium Enterprises (MSMEs) which operates in the field of serving food and drinks which is currently developing in Pontianak. In this juice business, the problem lies in using inappropriate basic ingredients which can cause less than optimal profits. This research was conducted with the aim of formulating solutions to problems in optimizing profits for Micro, Small and Medium Enterprises (MSMEs) from the Sandra Juice business. The simplex method is a way to solve linear programming cases where repeated mathematical procedures are carried out to test corner points so that the optimal solution is found. The data used in this research are the results of Jus Sandra's business interviews. Based on the simplex linear method program, optimization calculation results were obtained including the amount of juice production being 25 glasses per day, so that a maximum profit of IDR 500,000 was obtained.